The Application of Digital Marketing as the Development of Online Marketing for UMKM in Tirto Hamlet to Increasing Productivity in the Era of Digital Market Competition - Loniza Erika; Juniar Hartono Rani; Chairunnisa Kurnia (SHS Web of Conferences)
Micro, Small, and Medium Enterprises (UMKM) in Tirto Hamlet have not implemented digital marketing and have not realized the big role they play in the use of this method. Service activities use the socialization method with the theme of the role of digital marketing for UMKM business development, especially in terms of increasing promotional activities, determining target markets and using the marketplace. The socialization participants came from a long-established palm sugar and handicraft production business in Tirto Hamlet, and the implementation location was at the Tirto Hamlet Hall. This socialization was followed enthusiastically by the participants which was realized through questions and answers and giving door prizes to participants who asked. At the end of the event, a questionnaire was given regarding Digital Marketing Socialization in Tirto Hamlet, the results of which showed that on average the participants had knowledge of social media, but some did not use social media to promote their products. Therefore, it is hoped that this socialization can provide encouragement to UMKM players to take advantage of digital marketing so that the products produced can be widely traded